More than you think: An inclusive estimate of business entries - Dennis, William J. (Journal of Business Venturing, 1997)
The Wells Fargo/NFIB Series on Business Entries and Exits collected data throughout 1995 from 36,000 households regarding the business formation activity occurring among adults within those households. After adjusting for the 1.37 owners per firm and the 10% of households with more than one entry, there were an estimated 4.553-million business entries in the 12-month period involving 6.211 million active owners. Seventy-eight and one-half (78.5) percent of those businesses were de novo starts, 20.0% purchases, and the remainder other forms of entry (including missing responses). Most of the entries were quite small whether started or purchased. The number of business entries is significantly larger than prior estimates. However, the 4.553-million figure, when dissected into component parts, is consistent with other measures of business entry. The primary reason for the larger estimate is that this research was able to capture the significant number of very small entries that either do not appear in other databases or appear only after a substantial delay. These new data offer a significantly expanded view of the American business population and its dynamics. More specifically, they provide quantification of the smaller end of the entry scale, thereby introducing new population distributions and raising fundamental research and marketing questions about the unit of analysis (What is a business?) What constitutes a reasonable survey sample? To what population do we generalize survey data? What are the market segments of the small-business population, and how do they differ? What are the public policy requirements of these segments, and how do they coincide and conflict? And, what do real entry numbers tell us about the operation of the American economy on both a secular and cyclical basis? The foregoing are obvious. However, there are more subtle and perhaps more interesting questions. For example, the more people try to go into business for themselves, the more our collective (American) experience is influenced by the experience of business ownership. Small business draws enormous empathy from the American public; few Americans institutions are as popular. This is obviously a complex phenomenon. However, one explanation for its popularity is that so many Americans are exposed to business ownership either personally or through someone they know. Part of this research not yet published shows that small-business ownership pervades every class, income category, racial grouping, etc. The penetration of business formation into the American experience, therefore, is not only deep, it is also broad. And when its dimensions are so great, the remaining issue is not the existence of influence but its degree. If there are more starts than previously recognized, there must also be more exits. And, if there are more exits, the dynamics of the business entry-exit process become even more tumultuous than previously recognized. Particularly for those interested in either policy or management, the question becomes, “Why is exit so common?” One path of inquiry leads to motivation for entry, including career alternatives and income supplementation. To what extent do people intend to grow their businesses and to what extent do they intend their businesses to fill financial, occupational, or time gaps until something better comes along? Another path of inquiry leads to resources. Do resource constraints or constraints of other natures impede business development? Then there is the issue of preparation. How well-prepared are entrants? And, what reasonable steps can be taken to improve their assessments of potential opportunities or to effectively implement plans to capitalize on them? These are not necessarily new issues. But they become more conspicuous and pressing when the large number of exits is appreciated. The technique used to capture these data at a reasonable cost is called an “omnibus” or “caravan” survey. This survey technique is not well-known outside the commercial survey industry, but it presents considerable opportunity for researchers either with limited budgets or desirous of asking fewer than 10–15-minutes' worth of questions from a sample of the adult population. Its advantage is financial. Multiple sponsors can ask a limited number of proprietary questions at their own expense. But they then share the costs and results of reaching respondents and of asking the demographic questions, for example, age or sex of respondent. The current research posed two screen questions to all 36,000 households interviewed. The sponsors paid for those 72,000 questions. But only about 2,000 respondents passed one of the screens. These respondents were led through several more questions. Thus, the sponsors paid just for the screen questions and those questions administered to the 2,000. An extensive set of demographic data about the respondents was thrown in “free.”